Not acceptable to present taste: William Burges's great bookcase - Winterbottom, M (Decorative Arts Society, 2017)
Designed by William Burges and painted by fourteen young artists between 1859 and 1863, the ‘Great Bookcase’ was recently displayed for the first time at the Ashmolean Museum. Made to hold books on art and architecture, it is painted with a sophisticated iconographic scheme relating to the pagan and Christian arts. Despite acknowledging that it was not ‘acceptable to present taste’, Kenneth Clark’s acquisition of the bookcase for the Ashmolean in 1933 was remarkably far-sighted. Nevertheless, it was to take over eighty years before the bookcase was placed on public display at the museum.